Building an AIoT system emulator with Zephyr and QEMU - Ta, Anh Trung (Nanyang Technological University, 2025)
Internet of Things (IoT) and Artificial Intelligence (AI) are two of the emerging technologies of the recent years. While each technology is having its own prosperity in the tech ecosystem, innovators are attempting to combine them as one by incorporating AI into IoT systems with the name of AIoT.